State Legitimacy and Public Trust: A Constitutional Perspective on Government–Society Relations in Transitional Political Systems - Iskandar Syukur (GoAcademica Research & Publishing, 2024)
State legitimacy and public trust have emerged as central concerns in transitional political systems, where institutional instability and evolving constitutional frameworks often challenge the consolidation of democratic governance. While existing scholarship has extensively examined political legitimacy and citizen trust as separate constructs, limited attention has been given to their integration within a constitutional perspective. This study aims to analyze the relationship between state legitimacy and public trust by situating both within the framework of constitutional governance, with a particular focus on transitional political contexts. Employing a qualitative approach through a systematic literature review, this research synthesizes scholarly works indexed in Scopus and Web of Science over the past decade, focusing on key themes such as constitutionalism, institutional trust, and governance performance. The findings reveal that state legitimacy is not solely derived from formal constitutional arrangements but is significantly shaped by public perceptions of institutional performance, accountability, and the effective enforcement of the rule of law. Moreover, the study identifies a critical gap between normative constitutional design and empirical trust-building processes in transitional systems, often exacerbated by weak institutions and elite capture. This paper proposes a conceptual framework that links constitutional structures, institutional performance, public trust, and state legitimacy as an interconnected cycle. The study contributes to the literature by offering an integrative perspective that bridges constitutional theory and trust dynamics, providing both theoretical advancement and practical insights for strengthening governance in transitional democracies.